Correlations between circulating adipokines and hepatocellular carcinoma: a Systematic Review and meta-analysis - Ke, Yani; Pan, Yuyan; Huang, Xueru; Bai, Xing; Liu, Xiaojuan; Zhang, Mingsi; Jiang, Tao; Zhang, Guangji (Frontiers in Endocrinology, 2025)
BackgroundHepatocellular carcinoma (HCC) is among the most common malignant tumors, characterized by high incidence and mortality rates. The role of adipokines in liver diseases is increasingly recognized and involves multiple contributing factors. Therefore, we summarized the relationship between circulating adipokines and HCC to guide directions for future research.MethodsSix databases were searched, and all data were presented as standardized mean difference (SMD) or weighted mean difference (WMD). Sensitivity analysis and meta-regression were also performed. Diagnostic meta-analysis results were primarily presented using receiver operating characteristic (ROC) curves.ResultsA total of 41 articles were included in this meta-analysis. HCC patients had significantly higher levels of circulating adiponectin, leptin, visfatin, and resistin compared to the controls (SMD = 1.6, 95% CI: 0.65-2.56; SMD = 2.45, 95% CI: 1.59-3.31; SMD = 2.49, 95% CI: 1.32-3.65; SMD = 4.17, 95% CI: 3.17-5.17, respectively). Conversely, circulating irisin levels in HCC patients were significantly lower than those in the control group (WMD = -1.16, 95% CI: -1.55, -0.77). Subgroup analysis identified possible sources of heterogeneity, whereas meta-regression confirmed that only the presence or absence of viral hepatitis was the source of high heterogeneity among leptin-related studies. Additionally, the meta-analysis results of diagnostic studies show that circulating visfatin demonstrates good diagnostic value for HCC, which may be helpful for clinical practice.ConclusionThere is a significant association between circulating adipokines and HCC, and the presence of viral hepatitis is an influencing factor. Most adipokines are differentially expressed in HCC patients, and some may serve as biomarkers for early diagnosis or prognostic assessment.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023492972.